HES1 in immunity and cancer. (August 2016) - Rani, Aradhana; Greenlaw, Roseanna; Smith, Richard A; Galustian, Christine
Highlights: HES1 is regulated by the NOTCH signalling pathway as well as the wnt and hedgehog pathways. HES1 plays an important role in T cell development and cancer. HES1 represents a potent therapeutic target in cancer and leukaemia. Abstract: Hairy and enhancer of split homolog-1 (HES1) is a part of an extensive family of basic helix-loop-helix (bHLH) proteins and plays a crucial role in the control and regulation of cell cycle, proliferation, cell differentiation, survival and apoptosis in neuronal, endocrine, T-lymphocyte progenitors as well as various cancers. HES1 is a transcription factor which is regulated by the NOTCH, Hedgehog and Wnt signalling pathways. Aberrant expression of these pathways is a common feature of cancerous cells. There appears to be a fine and complicated crosstalk at the molecular level between the various signalling pathways and HES1, which contributes to its effects on the immune response and cancers such as leukaemia. Several mechanisms have been proposed, including an enhanced invasiveness and metastasis by inducing epithelial mesenchymal transition (EMT), in addition to its strict requirement for tumour cell survival. In this review, we summarize the current biology and molecular mechanisms as well as its use as a clinical target in cancer therapeutics.